2006
DOI: 10.1021/cc060068w
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Synthesis of Arrays of Amino-Acid-Derived Isocyanoamides Useful As Starting Materials in IMCR

Abstract: Arrays of amino-acid-derived isocyanoamides are conveniently produced on a multigram scale in one step by the solventless aminolysis of the corresponding methyl esters with primary or secondary aliphatic amines. Most of the corresponding isocyanides precipitate during the reaction and can be filtered to yield highly pure, colorless, and odorless solids. They are potentially useful in the combinatorial chemistry of multicomponent reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 39 publications
0
42
0
1
Order By: Relevance
“…The protocol was then extended to prepare few isoselenocyanato carboxamides also. Unlike esters and α‐isocyano carboxamides are stable solids and odorless but retain the isocyanide reactivity in isocyanide based multicomponent reactions (IMCRs)47, 48. Four complementary protocols are available to access this important starting material48, 49.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The protocol was then extended to prepare few isoselenocyanato carboxamides also. Unlike esters and α‐isocyano carboxamides are stable solids and odorless but retain the isocyanide reactivity in isocyanide based multicomponent reactions (IMCRs)47, 48. Four complementary protocols are available to access this important starting material48, 49.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike esters and α‐isocyano carboxamides are stable solids and odorless but retain the isocyanide reactivity in isocyanide based multicomponent reactions (IMCRs)47, 48. Four complementary protocols are available to access this important starting material48, 49. To implement our other objective in making α‐isoselenocyanato carboxamides 5 (Figure 3), six known α‐isocyano carboxamides were made employing known procedure.…”
Section: Resultsmentioning
confidence: 99%
“…[10] We have recently reported that the chiral aluminum-salen (salen = N,N-bis(salicylidene)ethylenediamine) complex [11] was an efficient catalyst for the enantioselective Passerini three-component reaction. [14,15] As a prelude of our work, we examined the reaction of the preformed imine 6 a (R 1 = tBu) and the a-isocyanoacetamide 4 a (R 2 = Bn) [16] in the presence of chiral phosphoric acids. To the best of our knowledge, there is no single report on Ugi-type reactions which involve the a addition of isocyanides to imines for generating the chiral centers.…”
Section: Tao Yue Mei-xiang Wang* De-xian Wang Gøraldine Masson Anmentioning
confidence: 99%
“…(1)]. [1,16] Therefore,b roader exploration of the reactivity profiles of both aryl isocyanides and isocyanoacetamides remains highly desirable. [10][11][12] Meanwhile, isocyanoacetamides are mainly known for the carbene-like reactivity of the isocyano group when used as af ive-atom component in multicomponent reactions [1,13] or palladiumcatalyzed imidoylative cyclization reactions, [14] and the acarbon atom of isocyanoacetamides has only been shown to serve as anucleophile in formal [3+ +2] cycloaddition [1,10,15] and alkylation reactions.…”
mentioning
confidence: 99%